Phase II study of pegylated liposomal doxorubicin, low‐dose dexamethasone, and lenalidomide in patients with newly diagnosed multiple myeloma. Issue 1 (January 2014) - Baz, Rachid C.; Shain, Kenneth H.; Hussein, Mohamad A.; Lee, Ji‐Hyun; Sullivan, Daniel M.; Oliver, Elizabeth Finley; Nardelli, Lisa A.; Nodzon, Lisa A.; Zhao, Xiuhua; Ochoa‐Bayona, Jose Leonel; Nishihori, Taiga; Dalton, William S.; et al.
<x xml:space="preserve">Abstract</x> Our previous phase I/II trial of pegylated liposomal doxorubicin (PLD), low‐dose dexamethasone, and lenalidomide in patients with relapsed and refractory myeloma showed an overall response rate of 75%, with 29% achieving ≥ VGPR. Here, we investigated this combination (PLD 30 or 40 mg/m2 intravenously, day 1; dexamethasone 40 mg orally, days 1–4; lenalidomide 25 mg orally, days 1–21; administered every 28 days) in a phase II study in patients with newly diagnosed symptomatic multiple myeloma to determine its efficacy and tolerability (ClinicalTrials.gov NCT00617591). At best response, patients could proceed with high‐dose melphalan or with maintenance lenalidomide and dexamethasone. In 57 patients, we found that the overall response rate and rate of very good partial response and better on intent‐to‐treat, our primary endpoints, were 77.2% and 42.1%, respectively, with responses per the International Myeloma Working Group. Median progression‐free survival was 28 months (95% CI 18.1–34.8), with 1‐ and 2‐year overall survival rates of 98.1 and 79.6%. During induction, grade 3/4 toxicities were neutropenia (49.1%), anemia (15.8%), thrombocytopenia (7%), fatigue (14%), febrile neutropenia (8.8%), and venous thromboembolic events (8.8%). During maintenance, grade 3/4 toxicities were mainly hematologic. We found this combination to be active in patients with newly diagnosed myeloma, with results comparable to other lenalidomide‐based induction strategies without proteasome inhibition. In addition, maintenance therapy with lenalidomide was well tolerated. Am. J. Hematol. 89:62–67, 2014. © 2013 Wiley Periodicals, Inc.